Collagenase-based wound debridement agent induces extracellular matrix supporting phenotype in macrophages - Pradipta Banerjee; Amitava Das; Kanhaiya Singh; Savita Khanna; Chandan K. Sen; Sashwati Roy (Scientific Reports, 2024)
Abstract Macrophages assume diverse phenotypes and functions in response to cues from the microenvironment. Earlier we reported an anti-inflammatory effect of Collagenase Santyl® Ointment (CSO) and the active constituent of CSO (CS-API) on wound macrophages in resolving wound inflammation indicating roles beyond debridement in wound healing. Building upon our prior finding, this study aimed to understand the phenotypes and subsets of macrophages following treatment with CS-API. scRNA-sequencing was performed on human blood monocyte-derived macrophages (MDM) following treatment with CS-API for 24 h. Unbiased data analysis resulted in the identification of discrete macrophage subsets based on their gene expression profiles. Following CS-API treatment, clusters 3 and 4 displayed enrichment of macrophages with high expression of genes supporting extracellular matrix (ECM) function. IPA analysis identified the TGFβ-1 pathway as a key hub for the CS-API-mediated ECM-supportive phenotype of macrophages. Earlier we reported the physiological conversion of wound-site macrophages to fibroblasts in granulation tissue and impairment of such response in diabetic wounds, leading to compromised ECM and tensile strength. The findings that CSO can augment the physiological conversion of macrophages to fibroblast-like cells carry significant clinical implications. This existing clinical intervention, already employed for wound care, can be readily repurposed to improve the ECM response in chronic wounds.